Wind characteristics and wind energy potential analysis in five sites in Lebanon - Al Zohbi, Gaydaa; Hendrick, Patrick; Bouillard, Philippe (International Journal of Hydrogen Energy, 2015)
Abstract The Lebanese electricity sector goes through a long crisis since the Lebanese civil war, marked by persistent rationing (demand is always greater than supply), mismanagement and a growing debt. This study aims at investigating the wind characteristics using actual wind data for five sites in Lebanon: Klaiaat, Cedars, Daher El Baydar, Marjyoun and Quaraoun. It was found that all sites have mean annual wind speeds greater than 3 m/s at 10 m height. The numerical values of the shape parameter k ranged from 165 to 236 in Klaiaat and Daher El Baydar for the minimum and maximum values respectively, whereas the value of the scale parameter c ranged from 407 to 630 m/s in Cedars and Daher El Baydar for the minimum and maximum values respectively. In order to verify if the wind energy could resolve or reduce the Lebanese electricity crisis, a study is elaborated on the monthly power produced by 116 wind turbines Enercon rated at a maximum 750 MW each that could be erected in five selected sites in Lebanon. The results show that the monthly based hourly electricity generated by these 116 wind turbines can cover the electricity demand during the night for whole months except August and September, and also a significant percentage of demand during daytime. Furthermore, the wind power could reduce the electricity crisis in Lebanon.
Keywords: Wind speed; Weibull parameters; Power law; Lebanon